Pengaruh Pemberian Jus Jambu Biji Dan Tomat Terhadap Lansia Yang Mengalami Konstipasi Di Panti Sosial Tresna Werdha Puspakarma Mataram - Nila Afriani; Niketut Sri Sulendri; Yuli Laraeni (Poltekkes Kemenkes Mataram, 2017)
Background. The elderly are groups of people who are undergoing a change. In the elderly tere is a decrease in the form of weakness. Decreased immune system and changes in organ function. Abnormalities due to changes in the gastrointestinal system result in a disorder that is constipation. Social House Tresna Werdha Puspakarma Mataram found elderly constipation. Research Purposes. The purpose of this study were to determine te effect of fluid constipastion and the influence of guava juice and tomato juice to the elderly who experienced constipastion. Research Methods. Method was analytical with design “Quasy Experiment” with research design non equevalen control group. The number of subjects in the study were 30 people. Research Result. Based on the results of research conducted showed that the average fluid consumed by all elderly were in the category of less thet was 1500 ml. The intervention group was significantly influenced by the average value of P < 0,05. Whereas in the control group there was no effect with the mean value P > 0,05. The results of the study of 15 people wo were given guava juice and tomato most of the respondents Decreased incidence of constipation as many as 14 people (93,3%) decreased constipation. In the control group with a sampel of 15 people, the number of constipated elderly were 13 people (86,6%). With the result of analysis there was a significant influence between guava juice and tomato juice with constipation with P < 0,005. Conclusion. There is a gift efeect guava juice and tomato juice against the constipated elderly in Social House Tresna Werdha Puspakarma Mataram.